Muslim perception of the modern secular state and the foundations of the Islamic State and commonwealth of nations (2014)
This paper seeks to explore the Muslim perception of the modern secular state by answering such questions as: Why do some Muslims and Muslim societies tend to reject the modern secular state and why do Muslims generally view Islam as "the lodestar" of politics? It examines the foundations of the Muslim perception of both the modern secular state and their rejection of comprehensive secularism. It also examines how this perception reflects a global Muslim commitment to both Islamic teachings and development without submitting to the secular modernist theory. Muslim engagement with secularism in countries such as modern Turkey and Malaysia shows that there is a need for the Islamic Commonwealth of Religions that fuses not Islam but religions in general with politics. This is because the Islamic Commonwealth of Religions does not make the other assimilate other dominant religious norms but only suppresses religious traditions and practices that are harmful and inimical to the other.